Trade Service Transformation in Digital Economy - A. O. Zvereva; E. Yu. Deputatova (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
Functioning of today's trade organization of wholesale and retail sectors has changed seriously. External trends are connected with the development of information technologies that envisages the necessity to use different innovation tools in business entities' work. The requirements to normative and legal base regulating the relations between participants of circulation sphere take into account the market dynamics and technology development and instruct trade enterprises to use in certain cases information systems and advanced digital means to conduct some operations in delivering goods to the customer. At the same time the introduction of digital products in practical work can promote rising of economic and social efficiency of trade enterprises, optimization of business-processes in industry organization and quality modification of trade services. The authors show that realization of all participants' interests in the chain 'trade organization - end-user' is possible in case of translation and introduction in business practice of trade structures innovations based on digital solutions.